(untitled) (Tanzania Journal for Population studies and Development, 2025)
Waste management is a major problem especially in the Global South. Examining the role of waste pickers in Tanga City, Tanzania, this study focuses on how these individuals affect livelihood, landfill sustainability, and environmental sanitation. Convenience sampling was deployed to obtain 20 landfill waste scavengers, and 15 street waste pickers; while a purposive sampling technique was used to select 4 key informants. Data was gathered through field observation, in-depth interviews, key informant interviews, and focus group discussions. The findings reveal that informal waste pickers are essential to recycling initiatives, landfill sustainability, and environmental sanitation because they help divert waste from landfills, lower greenhouse gas emissions, and minimize soil and water contamination. However, the dominance of formal waste collectors restricts the access by informal waste pickers to valuable recyclables, thereby limiting their contributions. Further, waste pickers confront a number of issues, such as economic vulnerability, dangerous working conditions, and social stigma. Notably, waste picking is a survival tactic used by marginalized urban populations in Tanga City. The study underscores the necessity of formal acknowledgement and policy integration of the waste pickers. The study further suggests that local governments should incorporate waste pickers into formal waste management systems through financial assistance, organizing waste picker unions, and legal recognition to increase their contribution and improve their standard of living. Additionally, capacity-building initiatives centred on recycling, composting, waste sorting, and biogas generation should be provided by the government.